Pengaruh Suhu Pengeringan Terhadap Kualitas Produk Gula Semut dari Nira - Meldayanoor Meldayanoor; Adzani Ghani Ilmannafian; Fitria Wulandari (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2019)
Kabupaten Tanah Laut has many sugar palm trees especially in the area of the ​​Guntung Besar and daerah Ranggang. But the manufacture of palm water in the area is only made into sugar print / brown sugar because the manufacture is more practical. If brown sugar is kept at room temperature, then brown sugar is easily melted. Therefore further processing is needed to maintain the quality of brown sugar. The purpose of this research is to make brown sugar with drying temperature variation. This research use ekspremental method with 4 treatment that is drying temperature 100oC, 75 oC, 50 oC, and control (without temperature drying). The test used in this research is pH test, water content test, ash content test and organoleptic test. The result shows that the pH value of sugar water used ranges from 6 to 7, the water content is 2,97% with the value of SNI maximal 3% and the ash content is 1, 98% with the value of SNI maximal 2, 0% at treatment A1 already fulfill SNI, Organoleptic test on flavor, aroma, texture and color obtained best result that is at treatment P1